2015
DOI: 10.1007/s10899-015-9570-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Within-Session Loss-Chasing: An Experimental Investigation of the Impact of Stake Size on Cognitive Control

Abstract: Loss-chasing is a central feature of problematic gambling, yet it remains a poorly conceived and understood concept. Loss-chasing is believed to stem from an erosion of cognitive control when gambling. The opportunity to gamble at significantly disparate stake sizes on a gambling activity is considered to be a risk factor for loss-chasing. This study investigated the impact of gambling at disparate stake sizes on executive processes integral to maintaining cognitive control when gambling, namely response inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…The negative association of gender with chasing suggests that males are more willing to chase losses than females. Although the majority of studies assessing chasing behavior have not examined gender differences (Bibby, 2016;Breen & Zuckerman, 1999;Campbell-Meiklejohn et al, 2008;Kim & Lee, 2011;Lister et al, 2016;Parke et al, 2016) or have not found gender differences (O'Connor & Dickerson, 2003;Worhunsky, Potenza, & Rogers, 2017), the results of the present study are in line with previous studies that have reported more persistent chasing behavior among male gamblers (Linnet et al, 2006;Nigro et al, 2018aNigro et al, , 2018b. Male gender was also associated with steep discounting rates and high craving levels, probably due to the high prevalence of problem gambling among males compared to the female population Cosenza, Ciccarelli, & Nigro, 2018, 2019Cosenza & Nigro, 2015;Hing, Russell, Tolchard, & Nower, 2016;.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The negative association of gender with chasing suggests that males are more willing to chase losses than females. Although the majority of studies assessing chasing behavior have not examined gender differences (Bibby, 2016;Breen & Zuckerman, 1999;Campbell-Meiklejohn et al, 2008;Kim & Lee, 2011;Lister et al, 2016;Parke et al, 2016) or have not found gender differences (O'Connor & Dickerson, 2003;Worhunsky, Potenza, & Rogers, 2017), the results of the present study are in line with previous studies that have reported more persistent chasing behavior among male gamblers (Linnet et al, 2006;Nigro et al, 2018aNigro et al, , 2018b. Male gender was also associated with steep discounting rates and high craving levels, probably due to the high prevalence of problem gambling among males compared to the female population Cosenza, Ciccarelli, & Nigro, 2018, 2019Cosenza & Nigro, 2015;Hing, Russell, Tolchard, & Nower, 2016;.…”
Section: Discussionsupporting
confidence: 87%
“…The ChasIT mainly investigates within-session chasing. Although the DSM-5 (APA, 2013) refers to chasing as "often returns another day to get even" (between-session chasing), researchers have demonstrated that the between-session and within-session chasing are highly correlated (Nigro et al, 2018a;Parke et al, 2016), so concluding that "a 'within-session' conceptualization is a useful point of departure for understanding the individual determinants of chasing" (Breen & Zuckerman, 1999;p. 1098).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between-session loss-chasing occurs, as the name suggests, over a longer period of time and may include multiple gambling sessions (Lesieur 1977). The majority of research has investigated within-session loss-chasing, where an individual attempts to recoup losses within a single session (Parke et al 2016). Behavioural economic perspectives attribute loss-chasing to a convex function linking accumulating monetary losses to only diminishing marginal reductions in subjective value or utility, promoting further risk-seeking choices (Kahneman and Tversky 1979;Kahneman and Tversky 2000).…”
Section: Introductionmentioning
confidence: 99%